Flavonoid-rich extract of unripe Terminalia catappa Modulates Redox Status and Aging in Lead-Induced Neuro-genotoxic Drosophila (Gadau Journal of Pure and Allied Sciences, 2024)
Terminalia catappa (Indian almond) fruit is an oval fruit in shape, growing on a large tree found mostly in the tropical region. The tree has wide health applications and benefits various African and Asian communities. However, there is little documented evidence of its effects on neuroprotection and longevity. This study explored the neuroprotective potential of the flavonoid content from the unripe fruit part of the plant against lead-induced neurogenotoxicity in a fly model (Drosophila melanogaster). Two to three days old male and female flies were harvested and used for the experiment. Negative geotaxis and flies’ pupation assays were employed for the assessment of the flies' behavior. Phase II antioxidant enzymes’ activities and their expression levels were evaluated to ascertain the redox status of the flies before and after the toxicants exposure.  Following the effective dose determination assay, 3.0 and 5.0 mg/g diets were found to be highly effective, meanwhile a concentration of 0.1 µg/g diet of lead (Pb) successfully induced neuro and genotoxicity. There was a remarkable improvement in the emergence of new and the locomotor function of the matured flies fed with the extract before their exposure to the toxic environment compared to the control group. Significant increase in the activity of Catalase, Superoxide dismutase (SOD), and Glutathione-s-transferase (GST) with concurrent reduction of AChE activity in the extract pre-fed flies. A similar effect was also recorded in the mRNA expression level of the corresponding genes when evaluated using a polymerase chain reaction (qPCR). The collective findings of the present study revealed the potential neuro and gene protection effect of the studied extract through antioxidant and antiaging enzyme activities against Lead-induced toxicity in D. melanogaster. Showcasing the potential of the fruit as a source of nutraceuticals that could improve the wellness and quality of human lives when further studied.
Keywords: Drosophila melanogaster; Environmental Toxicant; Lead; Longevity; Neurotoxicity; Terminalia catappa